2011
DOI: 10.1017/s1041610211000226
|View full text |Cite
|
Sign up to set email alerts
|

Animal-assisted activity and emotional status of patients with Alzheimer's disease in day care

Abstract: In this sample of severe AD patients in ADCC, AAA was associated with a decrease in anxiety and sadness and an increase in positive emotions and motor activity in comparison with a control activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
1
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 27 publications
8
76
1
8
Order By: Relevance
“…Clear patterns of reduced anxiety were observed in the intervention group. This supports previous studies that have reported the anxiety-reducing effects of service dogs in mental health patients (e.g., Lang et al 2010;Mossello et al 2011), and extends this to show that pet dogs can bring similar benefits.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Clear patterns of reduced anxiety were observed in the intervention group. This supports previous studies that have reported the anxiety-reducing effects of service dogs in mental health patients (e.g., Lang et al 2010;Mossello et al 2011), and extends this to show that pet dogs can bring similar benefits.…”
Section: Discussionsupporting
confidence: 91%
“…Parental reports suggest that the presence of an assistance dog in the home results in reduced child anxiety, and this is supported by decreases in cortisol awakening responses in these children following placement of the dog, which increase again following removal of the animal (Viau et al 2010). Indeed, there is mounting evidence to highlight the potential benefits of animals in reducing anxiety in a range of mental health disorders, including schizophrenia (Lang et al 2010) and Alzheimer's Disease (Mossello et al 2011). Other benefits reported by parents in these studies include decreased problematic behavior of the child, increased sense of security for the parents, and increased social acknowledgement for family members.…”
mentioning
confidence: 99%
“…The animalassisted activity contributed to increased motor activity of the participants. [3] Another study evaluated the effects of an animal-assisted therapy intervention on elderly nursing home patients affected by psychiatric diseases including dementia. Participants held, stroked, walked, talked to, and played with dogs during 90-minute weekly sessions.…”
Section: Introductionmentioning
confidence: 99%
“…Bunların dışında HDU; depresif semptomları olan hastalarda duygu durumunu iyileştirmekte, oksitosin aktivasyonu yolu ile agresyonu azaltmakta, empati ve öğrenmeyi arttırmaktadır 35,36,37 . Psikiyatrik sorunu olanlarda öz yeterlilik düzeyini ve yaşam kalitesini arttırdığı belirtilen uygulamalar; Alzheimer hastalarında da anksiyeteyi ve üzüntü halini azaltmakta, olumlu duyguları ve motor aktiviteyi arttırmaktadır 8,12 . Ayrıca, ileri yaştaki uzun dönem bakım hastalarında yalnızlık duygusunu azaltan, elektrokonvülsif tedavi uygulanan psikiyatri hastalarında tedaviye bağlı korkuyu azaltan HDU, demansı olan yaşlılarda ajite davranışları azaltmakta ve sosyal ilişkileri geliştirmektedir 7,10,13,14,43 .…”
Section: Hayvan Destekli̇ Uygulamalarin Yararlariunclassified